1995
DOI: 10.2307/3236224
|View full text |Cite
|
Sign up to set email alerts
|

Stand dynamics, regeneration patterns and long‐term continuity in boreal old‐growth Picea abies swamp‐forests

Abstract: Abstract. The occurrence of macrofossil charcoal (long axis > 0.5 mm) and Picea abies (Norway spruce) pollen in peat stratigraphies, in combination with size and age data from 2976 P. abies trees were used to analyse ecosystem continuity and stand‐structure in ten old‐growth swamp‐forests in northern Sweden. All stands were dominated by P. abies, a species whose abundance increased westwards in Sweden between 3000 and 2000 yr B.P. In three stands no macrofossil charcoal was found and the maximum age of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 37 publications
(40 reference statements)
6
76
0
2
Order By: Relevance
“…The peak at high cohort age consists of climax-type old-growth spruce forests that occur on rarely burning spruce swamps or on sites that are isolated by mires. Such old-growth spruce forests are important in actual landscapes with intermediate fi re frequencies (Zackrisson and Östlund 1991, Hörnberg et al 1995, Esseen et al 1997.…”
Section: Spatially Explicit Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak at high cohort age consists of climax-type old-growth spruce forests that occur on rarely burning spruce swamps or on sites that are isolated by mires. Such old-growth spruce forests are important in actual landscapes with intermediate fi re frequencies (Zackrisson and Östlund 1991, Hörnberg et al 1995, Esseen et al 1997.…”
Section: Spatially Explicit Simulationsmentioning
confidence: 99%
“…Studies suggest fi re intervals of 40-70 y in the 1800s, about 130 y in the 1600s and about 200 y around 1700 y BP, but it is not clear over what regions such fi gures could be extrapolated (Pitkänen and Huttunen 1999, Niklasson and Granström 2000, Pitkänen and Grönlund 2001. The longest fi re intervals have been observed on spruce swamps (Hörnberg et al 1995), in northern high-elevation forests (Steijlen andZackrisson 1987, Hyvärinen andSepponen 1988), and in European Russia outside Fennoscandia (Syrjänen et al 1994, Wallenius 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that even peatlands can burn fairly frequently (Tolonen 1985, Segerström et al 1994, Pitkänen et al 1999. Nevertheless, some studies indicate that there are forested sites, which have not been burnt for very long periods (Steijlen and Zackrisson 1987, Zackrisson et al 1995, Kuuluvainen et al 1998. Some evidence exists that Picea forest probably burn more seldom than Pinus forests (Zackrisson 1977, Engelmark 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In areas with harsh climate the occurrence of suitable microsites for seedlings and saplings, providing better conditions for their survival and growth, is an important aspect of phytocoenosis regeneration (Harmon et al 1986;Kuuluvainen 1994;Hörnberg et al 1995;Kupferschmid and Bugmann 2005a). The presence of different types of microsites creates diverse environmental conditions in terms of temperature, moisture, and light.…”
Section: Introductionmentioning
confidence: 99%